Applications of Instrumental Methods for Food and Food By-Products Analysis - Górska, Agata (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
The analysis of food and food by-products is a particularly important topic dealing with the development and application of various analytical procedures and methods determining the properties and safety of food and food constituents. It is an important tool not only for defining food quality but also for supporting the investigation of new food products and technologies. The continuous development of methodology and access to modern research equipment enable detailed research on the composition, structure, physicochemical properties, thermal characteristics, and stability of food products and, recently, also byproducts of the food industry, which are potentially a source of bioactive compounds and currently present little commercial value and are mostly disposed of as an industrial waste. It is imperative to identify the properties and potential applications of food by-products, which would fit in with current trends in circular ecology. Taking the aforementioned reasons into account, it is important to present procedures and instrumental analytical techniques and methods commonly used to analyze food and food processing byproducts and to discuss their application in food research to detect and characterize specific food components of significance to food science and technology, such as lipids, proteins, and carbohydrates.